Democratic decentralisation through a natural resources lens: an introduction - Larson, A.M.; Ribot, J.C. (2004)
It is simultaneously published in Ribot, J.C. and Larson, A.M. 2005. Democratic decentralisation through a natural lens. London, Routledge. pp. 1-25